Adam's Test #2. - Driscoll, Helen Rose. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: was fitted for a back brace to correct my scoliosis when I was eleven years old. My family, doctors, and I decided a "soft" or "flexible" brace was the best option for me even though it was a relatively new form of treatment. After years of art making, I turned my gaze from the external to the internal and began looking back to my physical and emotional trauma surrounding my years in the brace.